2009
DOI: 10.1093/jxb/erp361
|View full text |Cite
|
Sign up to set email alerts
|

Heteroplasmy and stoichiometric complexity of plant mitochondrial genomes--though this be madness, yet there's method in't

Abstract: Mitochondrial heteroplasmy is defined as the coexistence of divergent mitochondrial genotypes in a cell. The ratio of the alternative genomes may be variable, but in plants, the usually prevalent main genome is accompanied by sublimons--substoichiometric mitochondrial DNA (mtDNA) molecules. Plant mitochondrial heteroplasmy was originally viewed as being associated with pathological mutations or was found in non-natural plant populations. Currently, it is considered to be a common situation in plants. Recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
155
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(159 citation statements)
references
References 87 publications
3
155
1
Order By: Relevance
“…The AC frequency for short repeats in Viscum mtDNA is markedly higher than in the nine other angiosperm mtDNAs for which AC frequency has been measured by high-depth genome sequencing and also is higher than in angiosperms in which nongenome-scale approaches have been used (59). Not even a single AC was detected for the vast number (>300,000 and >70,000) of short-repeat pairs (30-100 bp in length) present in the mitogenomes of S. conica (11.3 Mb) and cucumber (1.7 Mb), respectively (9, 60).…”
Section: Abundant Repeats and Extreme Levels Of Recombination And Submentioning
confidence: 71%
See 1 more Smart Citation
“…The AC frequency for short repeats in Viscum mtDNA is markedly higher than in the nine other angiosperm mtDNAs for which AC frequency has been measured by high-depth genome sequencing and also is higher than in angiosperms in which nongenome-scale approaches have been used (59). Not even a single AC was detected for the vast number (>300,000 and >70,000) of short-repeat pairs (30-100 bp in length) present in the mitogenomes of S. conica (11.3 Mb) and cucumber (1.7 Mb), respectively (9, 60).…”
Section: Abundant Repeats and Extreme Levels Of Recombination And Submentioning
confidence: 71%
“…In angiosperm mitochondria, low-abundance substoichiometric DNA molecules (termed "sublimons") are often present, arising via recombination between short repeats (57)(58)(59). Most pairs of repeats in Viscum mtDNA are short; of those ≥30 bp in size, 97% (305 of 315) are ≤100 bp in length, and 86% of these are <50 bp in length.…”
Section: Abundant Repeats and Extreme Levels Of Recombination And Submentioning
confidence: 99%
“…Unlike the small (15-18 kb) and homogenous mitochondrial genomes of animals, plant mitochondrial genomes are large (hundreds of kb or more) and complicated, with dramatic variations in structure, size, and organization [2]. Studies have shown that in the angiosperm mitochondrial genomes, frequent DNA recombination may result in genomic rearrangements, yielding multiple types of recombinant structures that may vary dramatically in copy number (substoichiometric shifting (SSS)); the recombinant structures may contain new open reading frames (ORFs) and some of them can cause cytoplasmic male sterility (CMS) [3][4][5]. CMS is a widespread phenomenon observed in more than 150 flowering plant species [6] and often associated with unusual ORFs present in the mitochondrial genomes [5].…”
Section: Introductionmentioning
confidence: 99%
“…When these repeated sequences are in direct orientation, they allow the genome to be subdivided into a collection of molecules, each containing only a portion of the genetic information. These molecules of plant mitochondrial DNA can vary in copy number over time, a process called substoichiometric shifting (Small et al, 1987;Janska et al, 1998;Abdelnoor et al, 2003) that leads to heteroplasmic complexity (Woloszynska, 2010). Silencing of genes that control such shifting, such as the DNA mismatch repair protein MSH1 that is homologous to mutator protein MutS in Escherichia coli (Abdelnoor et al, 2003), might be a good approach to solve the problem of plant transformation.…”
Section: Plantsmentioning
confidence: 99%